2005
DOI: 10.1111/j.1479-828x.2005.00470.x
|View full text |Cite
|
Sign up to set email alerts
|

Bleeding disorders in teenagers presenting with menorrhagia

Abstract: Severity of menstrual loss was not predictive of a bleeding disorder, as a significant cause of teenage metrostaxis is due to anovulatory dysfunctional uterine bleeding. The authors recommend that a careful personal and family history of bruising and bleeding be taken in all teenagers who present de novo with menorrhagia. Routine screening in a primary care setting is impractical, but should be mandatory in all patients with a positive family history.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
41
1
7

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(50 citation statements)
references
References 18 publications
1
41
1
7
Order By: Relevance
“…In a retrospective study of 106 adolescents with menorrhagia, 11 (10.4%) patients were found to have an underlying bleeding disorder. A positive family history of bleeding symptoms was a significant predictor of a bleeding disorder in this study [124]. Acute adolescent menorrhagia requiring hospital admission is also a strong predictor of a bleeding disorder.…”
Section: Menorrhagiamentioning
confidence: 59%
See 1 more Smart Citation
“…In a retrospective study of 106 adolescents with menorrhagia, 11 (10.4%) patients were found to have an underlying bleeding disorder. A positive family history of bleeding symptoms was a significant predictor of a bleeding disorder in this study [124]. Acute adolescent menorrhagia requiring hospital admission is also a strong predictor of a bleeding disorder.…”
Section: Menorrhagiamentioning
confidence: 59%
“…This is likely to be due to immaturity of the hypothalamicpituitary-ovarian axis resulting in anovulatory cycles [118][119][120]. However, in a significant proportion of these cases, an underlying bleeding disorder may be identified [121][122][123][124]. Eight of 14 adolescents presenting with menorrhagia without thrombocytopenia who underwent comprehensive testing for a bleeding disorder had an underlying bleeding disorder [121].…”
Section: Menorrhagiamentioning
confidence: 99%
“…En la adolescencia las etiologías principales de SME son la anovulación por inmadurez del eje hipotála-mo-hipófisis-ovario y las coagulopatías congénitas o adquiridas en un porcentaje variable (10-62%) principalmente enfermedad de von Willebrand (3-36%) y disfunción plaquetaria (3-44%) 8,9,10 .…”
Section: Introductionunclassified
“…En 2007 se establece una definición cercana a la práctica clínica y centrada en la paciente, definiéndolo como una pérdida excesiva de sangre menstrual que interfiere con la calidad de vida física, social, emocional y/o material de una mujer que puede acompañarse o no de otros síntomas 4 . Esta definición se basa en estudios en mujeres adultas con SME donde se demostró que existe un impacto físico, social y psicológico y su tratamiento ha mostrado mejorar la calidad de vida de éstas 4,5,6,7 .En la adolescencia las etiologías principales de SME son la anovulación por inmadurez del eje hipotála-mo-hipófisis-ovario y las coagulopatías congénitas o adquiridas en un porcentaje variable (10-62%) principalmente enfermedad de von Willebrand (3-36%) y disfunción plaquetaria (3-44%) 8,9,10 .La prevalencia del SME en adolescentes no está bien definida, en parte, porque se puede considerar como normal dentro del desarrollo, tanto por la familia que no consulta o lo hace tardíamente, como por el equipo de salud que no explora o desestima este diagnóstico hasta no presentar complicaciones como sangrado importante, anemia aguda o crónica secundaria a las pérdidas excesivas de hierro. Además, las adolescentes podrían tener dificultad en reconocer un patrón de sangrado menstrual normal 3 y sus referentes, que son las otras mujeres de la familia, pueden haber tenido o tener SME, especialmente en el contexto de coagulopatía familiar, pese a esto, existen datos en Brasil, Malasia, Suecia, Nigeria e India que reportan prevalencias entre 1-37% 11,12,13,14,15 .…”
unclassified
“…19 Studies of adolescent populations with menorrhagia have shown the prevalence of IBDs to be 10-57%. 20,21 Strong predictors include menorrhagia from menarche, menorrhagia requiring hospital admission and a family history of bleeding symptoms. 22,23 Menstruation may be the first haemostatic challenge affected girls face and bleeding can be severe.…”
Section: Menorrhagia and Ibdsmentioning
confidence: 99%